The utilisation of statistics to estimate evaporation from the surface of solar ponds - Asaad Hameed Sayer; Hazim Al-Hussaini; Alasdair N. Campbell (University of Thi-Qar Journal of Science, 2021)
Renewable energies including solar energy offer the best opportunity to decrease greenhouse gases and introduce the necessary solutions to meet demand for energy. Solar ponds are a simple, and cost-effective way to collect and store incident solar radiation. The most widely used type is the salinity gradient solar pond (SGSP), which can provide large capacity, and supply thermal heat for year-round for a wide range of applications. Evaporation has been shown previously to be the major mode of heat loss from the surface of the SGSP. In the present study, the utility of linear regression analysis to create a reasonable model to describe the evaporation level from the surface of an open water body is investigated. The created models considered the climatic factors (the ambient temperature, relative humidity, wind speed, and solar radiation). Evaporation levels were also calculated utilizing equation of Kishore and Joshi (1984). The calculated levels using the two created models and Kishore and Joshi’s equation were compared with the measured evaporation at the local meteorological station for nine months. The results showed that good agreements were achieved, and the suggested statistical models could be used to calculate evaporation from the surface of a SGSP at any time when measurements of the ambient temperature, relative humidity, wind speed and solar radiation are available. The second model showed that solar radiation could be excluded from the calculation, and the results remained with an acceptable relative error.